Spatial Formation of Pesantren Pabelan : A Preliminary Study to Understanding Territory Delineation - Retna Hidayah (Universitas Negeri Yogyakarta, 2010)
Pesantren, a setting where muslim community –who embraced Islam religion- live together and learn about Islamic teachings intensively to become a good muslim, is considered as a unique of culture which characterized by special of life pattern, mores, and the presence of internal-authority hierarchy..Study on physical phenomena of pesantren is needed to understand pesantren as whole phenomena in both cultural and physical phenomena. This study was conducted to clarify spatial formation of pesantren Pabelan within Pabelan Village context as a broader setting where pesantren Pabelan was established. Data was gathered through multi-method data collection approaches consisting of observation, photographs, personal case history, and informal interview. This study verified that (1) spatial structure was arranged into concentric circle formation around Pabelan Mosque as a center of religious activity inthis village to maintain power structure, (2) Pesantren Pabelan is a unit of culture that was either separated or integrated with surrounding community, (3) Pesantren spatially segregated based on functional relationship, dominantly use of space, and domain separation between male and female.Key words: Pesantren, muslim community, spatial formation, territory delineation, traditional rural village, Indonesia